Recapitulating kidney development: Progress and challenges. (July 2019) - Little, Melissa H.; Kumar, Santhosh V.; Forbes, Thomas
Abstract: Decades of research into the molecular and cellular regulation of kidney morphogenesis in rodent models, particularly the mouse, has provided both an atlas of the mammalian kidney and a roadmap for recreating kidney cell types with potential applications for the treatment of kidney disease. With advances in both our capacity to maintain nephron progenitors in culture, reprogram to kidney cell types and direct the differentiation of human pluripotent stem cells to kidney endpoints, renal regeneration via cellular therapy or tissue engineering may be possible. Human kidney models also have potential for disease modelling and drug screening. Such applications will rely upon the accuracy of the model at the cellular level and the capacity for stem-cell derived kidney tissue to recapitulate both normal and diseased kidney tissue. In this review, we will discuss the available cell sources, how well they model the human kidney and how far we are from application either as models or for tissue engineering.